Sistem Hash Password dan Enkripsi AES-256 pada Website Rekam Medis Elektronik - Muhamad Misbahudin Sobirin; Asri Wulandari; Riza Adi Pratama (Jetri : Jurnal Ilmiah Teknik Elektro, 2023)
The rapid advancement of Information Technology demands efficient data management, especially within hospital settings to provide optimal services. Medical records play a crucial role in this context, encompassing patient health information stored by healthcare professionals. The transition towards electronic-based medical records is a prevailing trend, albeit accompanied by concerns regarding data security risks. Therefore, this study aims to implement a medical record data management system with a security approach that includes a password hashing system and AES-256 encryption. This research aims to design a password hashing system, encryption-decryption mechanism, and analyze the security level of password hashing against brute force attacks. The methodology focuses on utilizing the bcrypt algorithm for password hashing and the AES-256 algorithm for medical record data encryption. Test results indicate that the password hashing system utilizing the bcrypt algorithm generates secure hashes, and the AES-256 encryption system successfully encrypts medical record data with a 100% success rate. Brute force testing proves the effectiveness of the bcrypt algorithm in safeguarding password hash values. This research confirms that the implementation of password hashing and AES-256 encryption provides a robust layer of security in electronic medical record systems, supporting the transition towards safer and more efficient data management.